Infiltrating lipoma of oral cavity: A rare entity - Syed Wali Peeran; Karthikeyan Ramalingam; Fatma Mojtaba Alsaid; Marei Hamed Mugrabi (Wolters Kluwer Medknow Publications, 2013)
Introduction: Lipomas are rare in the oral cavity comprising less than 5% of benign neoplasms in head and neck region. Infiltrating lipomas are much less common than other variants. Case Report: We report a rare case of infiltrating/intra-muscular lipoma in the retro-molar region of a 28-year-old male. Discussion: To the best of our knowledge, this is the first case report from Libyan population and in the Middle East & North Africa region (MENA). Surgical excision is curative but, regular follow-up is needed to identify recurrences of this unusual variant.